Towards a heart-centred philosophy: Embracing poetry as transformative practice - Abraham, Danna (Murmurations: Journal of Transformative Systemic Practice, 2024)
Traditional educational practices often impose constraints on the connection between learners and their educational opportunities. A heart-centred philosophy serves as a response to the prevalent pedagogical methods entrenched in academic educational systems. The focus of this work is the transformative potential of poetry in fostering the conditions for the realisation of a heart-centred education. Poetry serves as a catalyst for establishing new forms of interaction with learners, while a heart-centred pedagogy stimulates a profound sense of liberation and connection that can flourish within the classroom. By encouraging learners to reflect on their personal narratives, ethical choices, and aspirations, the focus of concentration is to cultivate a space where critical thinking and emotional engagement while challenging traditional educational norms and empowering learners to embrace connection.